Snrnp25 is a candidate for the peri-implantation lethal phenotype of the Hba deletions - Ana María Velásquez-Escobar; Andrew E. Hillhouse; Terry Magnuson; David W. Threadgill (Mammalian Genome, 2025)
Mutations in adult hemoglobin alpha genes in humans lead to blood disorders commonly known as α-thalassemia. In search of a mouse model for this disease, mutagenesis screens have identified several deletions that resemble these phenotypes. The Hba b2(th) deletion, in particular, replicates the characteristics of alpha-thalassemia minor in heterozygous mice but presents a homozygous embryonic lethal phenotype. Previous analyses of Hba b2(th) mice suggested that the deletion affects both Hba genes ( Hba-a1 and Hba-a2 ) and considered epidermal growth factor receptor ( Egfr ) or rhomboid 5 homolog 1 ( Rhbdf1 ) to be responsible for the embryonic lethality. Molecular analysis of Hba b2(th) revealed a deletion spanning a 1 cM region of mouse chromosome 11. Importantly, the Hba b2(th) deletion does not extend to Egfr , indicating that the observed lethality of homozygous embryos is not due to the loss of Egfr . Sequence analysis of the Hba b2(th) deletion showed that the Hba-a2 gene is not deleted, but the lack of expression is likely due to the disruption of upstream regulatory regions. Furthermore, we identify Snrnp2 5, which codes for the small nuclear ribonucleoprotein 25 (U11/U12), as the candidate gene most likely responsible for the peri-implantation lethality of Hba b2(th) homozygous mice. These findings enhance the understanding of the genetic mechanisms underlying α-thalassemia and provide insights into novel genes essential for early mammalian development.

Host genetics and gut microbiota cooperatively contribute to azoxymethane-induced acute toxicity in Collaborative Cross mice - Chenhan Zhong; Li He; Sun-Young Lee; Hang Chang; Yuqing Zhang; David W. Threadgill; Ying Yuan; Fuling Zhou; Susan E. Celniker; Yankai Xia; Antoine M. Snijders; Jian-Hua Mao (Archives of Toxicology, 2021)

Derivation of stable embryonic stem cell-like, but transcriptionally heterogenous, induced pluripotent stem cells from non-permissive mouse strains - Tiffany A. Garbutt; Kranti Konganti; Thomas Konneker; Andrew Hillhouse; Drake Phelps; Alexis Jones; David Aylor; David W. Threadgill (Mammalian Genome, 2020)

Population-based dose–response analysis of liver transcriptional response to trichloroethylene in mouse - Abhishek Venkatratnam; John S. House; Kranti Konganti; Connor McKenney; David W. Threadgill; Weihsueh A. Chiu; David L. Aylor; Fred A. Wright; Ivan Rusyn (Mammalian Genome, 2018)

Erratum to: Status and access to the Collaborative Cross population - Catherine E. Welsh; Darla R. Miller; Kenneth F. Manly; Jeremy Wang; Leonard McMillan; Grant Morahan; Richard Mott; Fuad A. Iraqi; David W. Threadgill; Fernando Pardo-Manuel de Villena (Mammalian Genome, 2014)

Status and access to the Collaborative Cross population - Catherine E. Welsh; Darla R. Miller; Kenneth F. Manly; Jeremy Wang; Leonard McMillan; Grant Morahan; Richard Mott; Fuad A. Iraqi; David W. Threadgill; Fernando Pardo-Manuel de Villena (Mammalian Genome, 2012)

Genome-wide association mapping of loci for antipsychotic-induced extrapyramidal symptoms in mice - James J. Crowley; Yunjung Kim; Jin Peng Szatkiewicz; Amanda L. Pratt; Corey R. Quackenbush; Daniel E. Adkins; Edwin van den Oord; Molly A. Bogue; Hyuna Yang; Wei Wang; David W. Threadgill; Fernando Pardo-Manuel de Villena; et al. (Mammalian Genome, 2012)

Dietary fat-dependent transcriptional architecture and copy number alterations associated with modifiers of mammary cancer metastasis - Ryan R. Gordon; Michele La Merrill; Kent W. Hunter; Peter Sørensen; David W. Threadgill; Daniel Pomp (Clinical & Experimental Metastasis, 2010)

Dietary fat alters pulmonary metastasis of mammary cancers through cancer autonomous and non-autonomous changes in gene expression - Michele La Merrill; Ryan R. Gordon; Kent W. Hunter; David W. Threadgill; Daniel Pomp (Clinical & Experimental Metastasis, 2010)

The gastrointestinal microbiome: a malleable, third genome of mammals - Ian M. Carroll; David W. Threadgill; Deborah S. Threadgill (Mammalian Genome, 2009)

Replication and narrowing of gene expression quantitative trait loci using inbred mice - Daniel M. Gatti; Alison H. Harrill; Fred A. Wright; David W. Threadgill; Ivan Rusyn (Mammalian Genome, 2009)

Placental overgrowth and fertility defects in mice with a hypermorphic allele of epidermal growth factor receptor - Jennifer Dackor; Manyu Li; David W. Threadgill (Mammalian Genome, 2009)

Murine models of colorectal cancer - Joshua M. Uronis; David W. Threadgill (Mammalian Genome, 2009)

The Collaborative Cross at Oak Ridge National Laboratory: developing a powerful resource for systems genetics - Elissa J. Chesler; Darla R. Miller; Lisa R. Branstetter; Leslie D. Galloway; Barbara L. Jackson; Vivek M. Philip; Brynn H. Voy; Cymbeline T. Culiat; David W. Threadgill; Robert W. Williams; Gary A. Churchill; Dabney K. Johnson; et al. (Mammalian Genome, 2008)

Genotype × diet interactions in mice predisposed to mammary cancer: II. Tumors and metastasis - Ryan R. Gordon; Kent W. Hunter; Michele La Merrill; Peter Sørensen; David W. Threadgill; Daniel Pomp (Mammalian Genome, 2008)

The polymorphism architecture of mouse genetic resources elucidated using genome-wide resequencing data: implications for QTL discovery and systems genetics - Adam Roberts; Fernando Pardo-Manuel de Villena; Wei Wang; Leonard McMillan; David W. Threadgill (Mammalian Genome, 2007)

Quantitative PCR assays for mouse enteric flora reveal strain-dependent differences in composition that are influenced by the microenvironment - A. Deloris Alexander; Roger P. Orcutt; JaNell C. Henry; Joseph Baker; Anika C. Bissahoyo; David W. Threadgill (Mammalian Genome, 2006)

Meeting report for the 4th Annual Complex Trait Consortium Meeting: From QTLs to Systems Genetics - David W. Threadgill (Mammalian Genome, 2006)

Announcements - David W. Threadgill; Kent W. Hunter; Robert W. Williams (Mammalian Genome, 2002)

Genetic dissection of complex and quantitative traits: from fantasy to reality via a community effort - David W. Threadgill; Kent W. Hunter; Robert W. Williams (Mammalian Genome, 2002)

Genealogy of the 129 inbred strains: 129/SvJ is a contaminated inbred strain - David W. Threadgill; Delia Yee; Argabin Matin; Joseph H. Nadeau; Terry Magnuson (Mammalian Genome, 1997)

SSLPs to map genetic differences between the 129 inbred strains and closed-colony, random-bred CD-I mice - David W. Threadgill; Aragabin Matin; Delia Yee; Minerva M. Carrasquillo; Kenneth R. Henry; Karen G. Rollins; Joseph H. Nadeau; Terry Magnuson (Mammalian Genome, 1997)